A rare complication developing after delivery: septic pelvic thromboembophlebitis - Çintesun, Ersin; Bayramoğlu, Denizhan; Uysal, Emine; Çelik, Çetin (Perinatal Medicine Foundation, 2020)
Objective In this case report, we aimed to discuss a septic pelvic thromboembophlebitis (SPT) case detected 20 days later who had the previous history of cesarean section and had an intrauterine stillbirth vaginally at 30 weeks of gestation. Case(s) A 24-year old patient, who admitted to the emergency service with the complaints of fever and pain in the lower right abdomen and was reported to have a 4 cm formation consistent with thrombus on the right ovarian vein wall in the computed tomography (ST), was hospitalized for follow-up and treatment. The patient whose thrombus showed remission in the check-up tomography scan after the broad-spectrum antibiotherapy and anticoagulant treatment was discharged on the 10th day. The treatment of the patient who did not develop any complication in the follow-ups was completed with recover. Conclusion In conclusion, SPT is a complication which is seen rarely in both obstetric and gynecologic practices. SPT is a disease which may lead to fatal outcomes by late diagnosis but satisfying results with early diagnosis. Abdominal pain and fever symptoms should come to mind in all cases after delivery or operation.